Aroma Quality of Fruits of Wild and Cultivated Strawberry (FRAGARIASPP.) in Relation to the Flavour-Related Gene Expression - Bianchi Giulia; Lovazzano Andrea; Lanubile Alessandra; Marocco Adriano (Journal of Horticultural Research, 2014)
Expression profiles of flavour-related genes and the aroma quality of fruit headspace were investigated in the four strawberry genotypes ‘Reine des Vallées’ (Fragaria vesca), ‘Profumata di Tortona’ (F mos-chata), ‘Onda’ and VR 177 selection (F” x ananassa). Differences in the expression level of genes coding of strawberry alcohol acyltransferase (SAAT), F. x ananassa nerolidol synthase 1 (FaNESl) and F vesca monoterpene and sesquiterpene synthases (FvPINS and PINS1, respectively) were detected among these genotypes. In fruits of F. x ananassa the terpenoid profile was dominated by nerolidol, whereas wild spe–cies produced mainly monoterpenes. It was correlated with the higher induction of FaNES1 in cultivated and PINS gene in the wild Fragaria species. The flavour biogenesis in ripening fruits was determined by the expression of SAAT gene, especially visible for ‘Profumata di Tortona’ and ‘Onda’ strawberries. The fruit solid-phase microextraction (SPME) headspace was analysed using the Gas Chromatography-Olfac–tometry (GC-O), that allows for the chromatographic separation of volatiles together with their olfactomet-ric evaluation. ‘Reine des Vallées’ fruits have a peculiar profile characterized by high concentrations of limonene, linalool and mesifurane that resulted in “spiced”, “citrus, floral” and “sweet, baked” descriptors. The character impact compound in ‘Profumata di Tortona’ fruits was ethyl butanoate, responsible for “sweet” and “fruity, strawberry” descriptors. However, it was detected in lower amount in comparison to the data obtained for F. x ananassa strawberries. The sesquiterpene nerolidol was identified in both culti–vated strawberry genotypes.